Underground Mine Positioning: A Review - Soto-Gomez, J; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2022)
Underground mining is expected to lead the mining industry in the near future. Due to the advance of electronic devices and communications technologies, new safety regulations must be accomplished in order to operate underground mines safely and optimally. In 2006, the US government updated safety policies and introduced the PUBLIC LAW109-236. As a result, underground tracking is nowadays mandatory for underground mine operations. This new regulation establishes that current, or immediately pre-Accident location of all underground personnel must be delivered over ground. Despite the recent advances of tracking and positioning systems for indoor environments, underground mines are a unique scenario which poses different and highly demanding constraints for current technologies. Throughout this manuscript an extensive survey on underground mines positioning technologies is provided. The main characteristics of current localization systems in underground mines are analysed for their implementation from a user s requirements point of view. Furthermore, the main constraints and opportunities of the existing indoor positioning systems to deliver underground tracking are presented. Finally, future research directions are highlighted. © 2001-2012 IEEE.